Inhibition of c-Jun N-terminal kinase (JNK) suppresses porcine oocyte ageing in vitro - M. Sedmíková; J. Petr; A. Dörflerová; J. Nevoral; B. Novotná; T. Krejčová; E. Chmelíková; L. Tůmová (Czech Journal of Animal Science, 2013)
Oocyte ageing is a complex of processes that occur when matured in vitro oocytes are, after reaching the metaphase II stage, exposed to further in vitro culture. Aged oocytes remaining at the metaphase II stage undergo spontaneous parthenogenetic activation, or cellular death, through apoptosis (fragmentation) or lysis. The key factor in apoptotic pathway regulation is c-Jun-N-terminal kinase (JNK), stress kinase from the mitogene-activated protein kinase (MAPK) family. To investigate the effect of JNK inhibition on porcine oocytes ageing, cleavage rate, and embryonic development after parthenogenetic activation, DNA fragmentation, and pro-apoptotic factor Bax expression, we cultured in vitro matured oocytes for another 1-4 days in the presence of a JNK inhibitor. The inhibition of JNK significantly protected the oocytes from fragmentation (0% of fragmented oocytes under JNK inhibition vs. 13.4% of fragmented oocytes in the control group, 2nd day of ageing) and increased the percentage of parthenogenetically activated oocytes (82 vs 57.7%, 2nd day of ageing). The embryonic development of oocytes parthenogenetically activated after 24 h of ageing was influenced by JNK inhibition as well. The percentage of oocytes at the morula stage, after seven days of cultivation, was significantly increased when oocytes aged in the presence of a JNK inhibitor (42.5%) by comparison to the percentage of oocytes exposed to ageing in an inhibitor-free medium (23.3%). DNA fragmentation was significantly suppressed by JNK inhibition from the 1st day of ageing, but the expression of pro-apoptotic factor Bax in the oocytes was not influenced. On the basis of our experiments, we can conclude that JNK inhibition suppresses apoptosis and DNA fragmentation of aged oocytes and improves their embryonic development following the parthenogenetic activation. However, to completely eliminate all ageing related processes is insufficient.